Iktikat Baik Para Pihak dalam Pelaksanaan Mediasi di Pengadilan Agama - Lizuardi, Amiril; Sudirman, Sudirman; Izzuddin, Ahmad (De Jure: Jurnal Hukum dan Syari'ah, 2017)
This article aims to describe the principle of good faith in the Supreme Court Regulation No. 1 of 2016 concerning Mediation in the Court while at the same time describing the implementation of the principle of good faith in the conduct of mediation in the Malang District Religious Court. This research is included in empirical research using a qualitative approach. The results of the discussion of this article indicate that Mediation is an inseparable part of the procedure in the Religious Courts as stipulated in the Indonesian Supreme Court Regulation Number 1 of 2016 concerning Procedure for Mediation in Courts. In the Republic of Indonesia's Supreme Court Regulation Number, 1 of 2016, the provisions of good faith in the implementation of mediation were added. The mediator has the authority to evaluate the intentions of the parties during the mediation.Artikel ini bertujuan mendeskripsikan asas iktikad baik dalam Peraturan Mahkamah Agung RI Nomor 1 Tahun 2016 tentang Mediasi di Pengadilan sekaligus mendeskripsikan implementasi asas iktikad baik dalam pelaksanaan mediasi di Pengadilan Agama Kabupaten Malang. Penelitian ini termasuk dalam penelitan empiris dengan menggunakan pendekatan kualitatif. Hasil pembahasan artikel ini menunjukkan bahwa Mediasi merupakan bagian yang tidak dapat dipisahkan dari prosedur beracara di Pengadilan Agama sebagaimana diatur dalam Peraturan Mahkamah Agung RI Nomor 1 Tahun 2016 tentang Prosedur Mediasi di Pengadilan. Dalam Peraturan Mahkamah Agung RI Nomor 1 Tahun 2016 ditambahkan tentang ketentuan iktikad baik dalam pelaksanaan mediasi. Mediator memiliki wewenang untuk melakukan penilaian terhadap iktikad para pihak selama pelaksanaan mediasi.